Open Pore Ultrafiltration Hollow Fiber Membrane Fabrication Method via Dual Pore Former with Dual Dope Solution Phase - Kyunghoon Jang; Thanh-Tin Nguyen; Eunsung Yi; Chang Seong Kim; Soo Wan Kim; In S. Kim (Membranes, 2022)
Hollow-fiber membranes are widely used in various fields of membrane processes because of their numerous properties, e.g., large surface area, high packing density, mass production with uniform quality, obvious end-of-life indicators, and so on. However, it is difficult to control the pores and internal properties of hollow-fiber membranes due to their inherent structure: a hollow inside surrounded by a wall membrane. Herein, we aimed to control pores and the internal structure of hollow-fiber membranes by fabricating a dual layer using a dual nozzle. Two different pore formers, polyethylene glycol (PEG) and polyvinyl pyrrolidone (PVP), were separately prepared in the dope solutions and used for spinning the dual layer. Our results show that nanoscale pores could be formed on the lumen side (26.8–33.2 nm), and the open pores continuously increased in size toward the shell side. Due to robust pore structure, our fabricated membrane exhibited a remarkable water permeability of 296.2 ± 5.7 L/m2·h·bar and an extremely low BSA loss rate of 0.06 ± 0.02%, i.e., a high BSA retention of 99.94%. In consideration of these properties, the studied membranes are well-suited for use in either water treatment or hemodialysis. Overall, our membranes could be considered for the latter application with a high urea clearance of 257.6 mL/min, which is comparable with commercial membranes.